The role of digitalization of village-owned enterprises in equitable village economic growth - Utomo, Hardi (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
Studies related to Village-Owned Enterprises (BUMDes) have produced a lot of literature discussing the role of BUMDes in advancing the rural economy and improving the welfare of village residents. However, studies regarding the digitalization of BUMDes are still relatively limited. BUMDes digitalization refers to the use of digital information technology in carrying out various business activities carried out by BUMDes. The focus is to evaluate the feasibility of the Android-based BUMDes SAKU (Business Feasibility Analysis System) prototype. The methodology used is descriptive qualitative research with an expert testing method. Primary data was collected through questionnaires and interviews. Research respondents were divided into two groups, namely the first group consisted of experts who acted as validators, including business feasibility analysis experts, BUMDes experts, and system development experts, while the second group was the prototype users, represented by the BUMDes director who also serves as chairman of the BUMDes Forum at the Semarang Regency level. Validation results show that this prototype can present the data needed by BUMDes to assist in compiling a business feasibility analysis, with a success rate of 75 percent. As many as 70 percent of users stated that this prototype provided benefits in developing BUMDes businesses. The implementation of SAKU is a concrete step in encouraging the digitalization of BUMDes in their business activities and supporting the achievement of equitable economic growth at the village level.